2022
DOI: 10.3390/healthcare10030483
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Socio-Demographic Factors in Health-Seeking Behaviors among Bangladeshi Residents during the First Wave of COVID-19

Abstract: Background: Socio-demographic variability among nations and cultures highly influences health-seeking behavior (HSB) in managing endemic or pandemic diseases. The present study aimed to investigate the influence of socio-demographic factors on HSB among Bangladeshi residents during the first wave of COVID-19. Methods: A cross-sectional online survey was performed with Bangladeshi residents (60% male and 40% female; age range: 10–60 years or above) from May to July 2020. Information was collected from the parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 59 publications
1
16
1
Order By: Relevance
“…A prior study has revealed that men and women exhibit comparable help-seeking behaviours [26]. However, in the current study, it was observed that female students were more likely to seek the advice of a psychologist, and this nding was also present in the study of Mou, that is, women were more likely than men to take precautions [27,28]. The likelihood of contracting a disease, how well people respond to treatments, and how frequently they seek medical attention have all been found to be in uenced by sex and social circumstances [29].…”
Section: Main Ndingscontrasting
confidence: 41%
“…A prior study has revealed that men and women exhibit comparable help-seeking behaviours [26]. However, in the current study, it was observed that female students were more likely to seek the advice of a psychologist, and this nding was also present in the study of Mou, that is, women were more likely than men to take precautions [27,28]. The likelihood of contracting a disease, how well people respond to treatments, and how frequently they seek medical attention have all been found to be in uenced by sex and social circumstances [29].…”
Section: Main Ndingscontrasting
confidence: 41%
“…This is similar with a study done in Bangladesh. 32 This might be due to that younger age groups were not having sufficient knowledge on risk factors and consequences of NCDs.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative semi-structured questionnaire was adopted based on recent research conducted among African and Asian countries 16,19,43 . Respondents had enough time to construct and amend their answers before being sent back 14,55 . Participants were encouraged to remain in constant communication with the researchers to clarify any details regarding the research as needs arose.…”
Section: Approachmentioning
confidence: 99%
“…However, the rapidity of their implementation, coupled with the stringency of their enforcement, impact morbidity and mortality rates in practice across countries, certainly in the early phase of the pandemic 4,[9][10][11][12] . Bangladesh was no exception introducing several lockdowns and other measures at the start of the pandemic 13,14 . Initiatives included the closure of educational establishments, including universities [13][14][15][16] , with these measures subsequently having an appreciable impact on educational sectors 14,17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation